Simultaneous Determinations of Aflatoxins B , B , G , And G Using Hplc with Photodiode-Array (PDA) Detector in Some Foods Obtained from Yogyakarta, Indonesia - Abdul Rohman; Triwahyudi Triwahyudi (agriTECH, 2008)
A method has been validated for simultaneous determinations of aflatoxins B , B , G and G  using HPLC with photodiodearray (PDA) detector in some foods obtained from Yogyakarta. An optimum condition is reached using column ResolveTM C   (150 mm x 3.9 mm i.d; 5 μm). The mobile phase used is a mixture of methanolacetonitrilewater (17: 1819: 63 v/v) delivered isocratically at 1.2 ml/min. All aflatoxins were detected at 365 nm. The samples of food (corn, rice,and pea nuts) were obtained from local markets and super markets in Yogyakarta. The sample was prepared by solid phase extraction using a Florisil cartridge.The method revealed a good linearity for all aflatoxins evaluated by determination coefficients (r2) > 0.99. The recoveries of aflatoxins B , B , G and G  are 84.78; 82.14; 85.29; and 89.06 %, respectively. The detections limits are 13.20;9.36; 7.54; and 6.75 μg/L. The RSD values of intraday precisions are 0.38; 1.27; 3.09; and 1.76 %, respectively. Thevalidated method has been used to quantify the level of flatoxins in foods.